Repositioning The Ombudsman's Function in The National Legal System: A Dialectical Comparative Study With The Wilayatul Mazhalim Institutions in the Contemporary Era - Muhammad Firhansyah; H. Jalaluddin; Nuril Khasyi’in (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The Ombudsman of the Republic of Indonesia (ORI), as an auxiliary state institution, faces effectiveness challenges due to the recommendatory nature of its legal products. On the other hand, Islamic civilization has the institution of Wilayatul Mazhalim, known for its imperative executive-judicial power in restoring the people's rights from the tyranny of the ruler. This study aims to analyze the philosophical nature of the Ombudsman, dissect the working mechanisms of Wilayatul Mazhalim, and formulate a formulation for repositioning the Ombudsman's functions and authorities in the future through a dialectical comparative study. This legal research uses a juridical-normative method with a statutory approach, a conceptual approach, and a comparative legal approach. The data used are secondary data obtained using library methods and data analysis is carried out using qualitative methods. The results of the study indicate that the current executive weaknesses of the Ombudsman are rooted in its low constitutional position and the Magistrate of Influence paradigm that is inadequate for Indonesian bureaucratic culture. A dialectical synthesis with Wilayatul Mazhalim offers a repositioning model in which the Ombudsman is granted